Desistência ao tratamento de usuários de crack no centro de atenção pssicosocial em Campina Grande/PB - Rodrigues Junior, José Edison (2013)
This study aimed to analyze the phenomenon of abdication of monitoring/treatment of crack users in a CAPS AD in Campina Grande-PB. That s an exploratory , description approach ,whose theoretical focus was historical-dialect of public politics on alcohol and drugs. The information collected was realized by using the technique of semi-structured interviews, combined with the crack users registered in CAPS AD in Campina Grande between 2007 and 2011.The material collected was subjected to thematic analysis method, obtaining the extraction of the following categories and subcategories of analysis: CATEGORY 1: Factors of abdication of monitoring/treatment in CAPS AD in Campina Grande PB with subcategory 1.1. Abdication on their own , 1.2. To take work/employment, 1.3 . Search for more intensive treatment , 1.4. Due to relapse; CATEGORY 2 : Treatment/monitoring in CAPS AD to the subcategory, 2.1. The dependence of crack and family support as reasons that led to frequent CAPS AD. CATEGORY 3: Living with crack addiction without treatment/monitoring in CAPS AD with the subcategory, 3.1. Religiosity as a therapeutic tool .The results showed a distance between priority for community treatment and the reality where there is lack of information about this kind of treatment and the admission as a solution. The discourse about the abdication of treatment of crack users make reference to the importance of family support, to the influence for the phenomenon of relapse and the affection to religious conceptions. Although the subjects recognize the qualifications of CAPS AD treatment, they try by themselves or by family influence, another ways of hospitalization. This leads us to conclude that it is necessary reflection and assessment of the work of CAPS AD. Counting on the social changes and the need of answers that the phenomenon requires